Map of North America. - Daniel Burgess & Co. (Daniel Burgess [& Co.], 1845)
Map shows political boundaries, major cities, population statistics, length of rivers, and distances by sea; Mexico encompassing the Southwest; coloration encompassing Texas as part of the United States, with boundary lines present for independent Texas; areas of Indian habitation; Russian "possessions," British America, Greenland, Guatimala, and the West Indies. Includes explanation and notes. Scale [ca. 1:31,700,000].